Respon Pertumbuhan Jagung (Zea mays) Dengan Pemberian Urea Bersalut Zeolit Sebagai Nitrogen Lepas Lambat - Aina, Nur; Jumadi, Oslan; Hiola, St. Fatmah Hiola (Fakultas MIPA UNM, 2017)
Abstract. This study is an experimental research that aims to find out how the response of corn growth (Zea mays) with urea-coated zeolite as nitrogen release slowly, implemented from April to December 2017. The making of fertilizer is done in Biology Laboratory of East III Floor Department of Biology Faculty of Mathematics and Natural Sciences of Makassar State University. The cultivation and maintenance of maize was conducted at Greenhouse of Ecophysiology of Seraca Crops Research Institute (Balitsereal) Maros and Analysis of nitrogen data at Soil Laboratory of Agricultural Technology Assessment Institute (BPTP) Regency. Maros South Sulawesi. This research used Randomized Block Design (RAK) 3 grouping with Control, Urea, Phosphate, Potassium (UPK), UPK Zeolite 10%, UPK Zeolit 30%, and UPK Zeolit 50%. The corn variety used was HJ 21 Agritan. Observation parameters were stem circumference, leaf chlorophyll content, plant biomass (root, stem and leaves), cob weight, ear length, seed weight, leaf nitrogen and seed nitrogen. The technique of data origin is done by using variance analysis technique (F test) / ANOVA at the level of trust Î± = 0,05%. Then proceed with Duncan's advanced test using SPSS statistic program 20. The results showed that there was an interaction between zeolite-coated urea fertilizer on the yield of cob and corncob with different results on the other treatment. The best results on urea-coated zeolite treatment with 10% concentration. While for stem circumference, leaf chlorophyll content, plant biomass (root, stem and leaf), seed weight, leaf nitrogen and seed nitrogen showed no effect but when viewed the average result of urea coated application of zeolite with the highest 30% concentration.Keywords: The growth of corn, the application of urea zeolite coated, slow release fertilizersp., Thalassiosira sp., Probiotic Bacteria